Dual-Ion Co-Regulation System Enabling High-Performance Electrochemical Artificial Yarn Muscles with Energy-Free Catch States - Ren, Ming; Dong, Lizhong; Wang, Xiaobo; Li, Yuxin; Zhao, Yueran; Cui, Bo; Yang, Guang; Li, Wei; Yuan, Xiaojie; Zhou, Tao; Xu, Panpan; Wang, Xiaona; et al. (Nano-Micro Letters, 2023)
Artificial yarn muscles show great potential in applications requiring low-energy consumption while maintaining high performance. However, conventional designs have been limited by weak ion-yarn muscle interactions and inefficient “rocking-chair” ion migration. To address these limitations, we present an electrochemical artificial yarn muscle design driven by a dual-ion co-regulation system. By utilizing two reaction channels, this system shortens ion migration pathways, leading to faster and more efficient actuation. During the charging/discharging process, PF−6 ions react with carbon nanotube yarn, while Li+ ions react with an Al foil. The intercalation reaction between PF−6 and collapsed carbon nanotubes allows the yarn muscle to achieve an energy-free high-tension catch state. The dual-ion coordinated yarn muscles exhibit superior contractile stroke, maximum contractile rate, and maximum power densities, exceeding those of “rocking-chair” type ion migration yarn muscles. The dual-ion co-regulation system enhances the ion migration rate during actuation, resulting in improved performance. Moreover, the yarn muscles can withstand high levels of isometric stress, displaying a stress of 61 times that of skeletal muscles and 8 times that of “rocking-chair” type yarn muscles at higher frequencies. This technology holds significant potential for various applications, including prosthetics and robotics. Highlights: 1 The dual-ion co-regulation system shortens ion migration pathways, which endow the yarn muscle with high contractile stroke (34.7%) and contractile rate (9.4% s−1), more than twice that of the “rocking-chair” -type ion migration yarn muscles. 2 The yarn muscle shows high isometric stress of 18.4 MPa (61 times that of skeletal muscles) and 8 times the isometric stress of the “rocking-chair” -type yarn muscles at a higher frequency. 3 The intercalation reaction between PF−6 and collapsed carbon nanotubes allows the yarn muscle to achieve an energy-free high-tension catch state